Analysis of the Efficacy of Mindfulness Meditation in a Mutual Aid Group for Bipolar Disorder - Francisco A. Burgos-Julián; Cintia Díaz-Silveira; Raquel Ruiz-Íñiguez; Miguel A. Santed-Germán (Clínica y Salud. Investigación Empírica en Psicología, 2024)

(untitled)
Background: The bipolar disorder (BD) is a severe, disabling mental disorder characterized by phases of mania, hypomania, or depression. The present quasi-experimental study of 21 BD patients (Mage = 44 years, SD = 11.45, 6% women) compared the efficacy of a mutual aid group (MAG) with a MAG that followed a mindfulness-based intervention (MAG+M) over 6 weeks. Method: Both groups were evaluated pre-test and post-test with the following variables: depression, mania, anxiety, mindfulness, and psychological acceptance. Results: Pretest and post-test intragroup analyses showed that MAG+M improved significantly in measures of depression (z = -2.31, p = .02) and trait anxiety (z = -2.43, p = .01), while MAG did not improve in any of the measures. There were no statistically significant differences between groups in the post-test. Conclusions: Our findings suggest that mindfulness meditation may improve symptoms of depression and anxiety in a MAG for BD patients.